Handbook of renal biopsy pathology - Howie, Alexander J. (Springer, 2008)
This practical handbook provides a short, clear and useful guide to interpretation of renal biopsy specimens. It is intended to be useful to pathologists, pathologists-in-training, nephrologists, nephrologists-in-training and medical students. Alexander J. Howie, M.D., is Professor of Renal Pathology, University College London, London, United Kingdom. General points about renal biopsy specimens -- Technical handling of renal biopsy specimens -- How to look at a renal biopsy specimen: preliminary study -- How to look at a renal biopsy specimen: initial study of the kidney -- Indication for biopsy: nephrotic syndrome -- Indication for biopsy: acute renal failure -- Indication for biopsy: chronic renal failure -- Indication for biopsy: hematuria -- Indication for biopsy: proteinuria -- Indication for biopsy: renal allograft -- Other indications for biopsy of kidneys.